Interação de genótipos de abobrinha italiana com inseticida no controle da broca das cucurbitáceas Diaphania nitidalis Cr. - Baldin, Edson Luiz Lopes [UNESP]; Lara, Fernando Mesquita [UNESP] (Sociedade Entomológica do Brasil, 1998)
A resistência de genótipos de abobrinha italiana Cucurbita pepo L. à broca das cucurbitáceas Diaphania nitidalis Cr. foi avaliada a campo. O genótipo Duda apresentou o maior número de frutos produzidos (33 frutos/parcela), enquanto Lita-186 foi o mais preferido, com a maior percentagem de frutos broqueados (3,6%). Os genótipos AG-202, Lita-186 e Duda, mais o inseticida deltametrina 25 CE foram avaliados. Duda comportou-se novamente como mais produtivo (35 frutos/parcela) e menos danificado (0,35%), confirmando os resultados obtidos no primeiro ensaio; já os genótipos AG-202 e Lita-186 revelaram-se os mais preferidos por D. nitidalis, com maiores índices de frutos danificados (2,7 e 6,3%, respectivamente).

Resistance to the pickleworm Diaphania nitidalis Cr. on squash genotypes Cucurbita pepo L. was evaluated in the field. The number of fruits and the percentage of the bored fruits were observed on the genotypes Caserta AG-202, HE-303, Clarice AG-772, Lita-186, Duda, and Novita. Genotype Duda produced the greatest number of fruits (33 fruits/plot). Genotype Lita-186 was the most preferred with the greatest number of damaged fruits (3.6), while genotype Duda was not damaged. Genotypes AG-202, Lita-186 and Duda, were selected to observe the interaction of squash genotypes with deltamethrin insecticide 25 CE to control the pickleworm. Genotype Duda was the most productive (35 fruits/plot) and least damaged one (0.35%), confirming the results of the 1st experiment. Genotypes AG-202 and Lita-186 were greatly preferred by D. nitidalis (2.7 and 6.3%, respectively).
Interaction of squash genotypes with insecticide on the control of the pickleworm Diaphania nitidalis Cr.
Keywords: Insecta; Lepidoptera; Pyralidae; Host plant resistance; Insecta; Lepidoptera; Pyralidae; Resistência de plantas